The Cold War and Working-Class Politics in the Coal Mining Communities of the Crowsnest Pass, 1945-1958 - Langford, Tom; Frazer, Chris (Labour/Le Travailleur, 2002)
Abstract This paper is concerned with the resilience of socialist workers' movements during the early years of the Cold War in Canada. Our study compares the workers' movements on either side of the BC/Alberta border in the Crowsnest Pass through the Rocky Mountains between 1945 and 1958. These are interesting movements because, although they were equally strong at the end of World War II, in the period in question one movement was very resilient (BC) and one suffered an electoral collapse. We found that the Cold War eroded the Labour Progressive Party's (LPP) electoral base in exactly the same way on the Alberta and BC sides of the Crowsnest Pass. Anti-communism was certainly promoted by extra-local sources of news and analysis such as newspapers, radio and movies, and was based upon international and national events. However, there were important local processes that amplified and concretized the more general forces, such as joint organizing against the LPP by a CCF leader and the Catholic Church in the Alberta Crowsnest, the recruitment of anti-communist miners from Eastern Europe, and the anti-communist stance of a roster of ethnic organizations. The resilience of the socialist workers' movement in the BC Crowsnest between 1945 and 1958 was due to a labour unity strategy which allowed Labour and the Left to deflect Cold War pressures and maintain mass electoral support among workers. It is significant that the strategy was built around a local organization (the Fernie and District Labour Party) which involved all of the unions in the area, and a local politician (Thomas Uphill) who had built up a dense network of personal support during his many years as MLA and mayor. The socialist workers' movement in the Alberta Crowsnest might have proven to be much more resilient in the 1950s had the LPP attempted to duplicate the successful labour unity strategy it had stumbled on in the BC Crowsnest.